Dakwah Dalam Pembentukan Karakter Peduli Lingkungan Anggota Crosser Gomang Trailcommunity Oleh Raden Mas Ansakhul Balaya Mangkunegara - Ardianita Angraeni, Cholifatul; Noviana Aini (Jurnal Multidisiplin Indonesia, 2023)
This thesis discusses preaching in the formation of the character of caring for the environment for cross members in the Gomang Trail Community by R.M. Ansakhul balaya Mangkunegara. The purpose of this study is to dig deeper and understand the uses and forms of Islamic da'wah that can be carried out through the trail community media. In this study the method used is qualitative. Data collection techniques used are observation, interviews and documentation. Based on research conducted on the Gomang Trail Community, from the findings in the field the authors know that the da'wah used by da'i in forming the character of caring for the environment towards crosser members in the Gomang Trail Community is preaching by carrying out positive activities aimed at forming the character of caring for the environment to members of the Gomang Trail Community Crosser Community. By doing social services to residents of remote villages and material assistance for the construction of mosques. These activities can change the character of cross members to be more concerned about others. This community also carries out nature conservation, such as helping the reforestation process in various areas and cleaning up the environment polluted by garbage. The activity aims to change the character of crossers so that they always preserve nature as a form of gratitude to God who has created the universe and everything in it. Holding regular recitations in forest.